Pengaruh Media Sosial Twitter Terhadap Wawasan Kebangsaan Remaja Indonesia dari Perspektif Psikologi Sosial - Nayla Rizqiyah; Dinie Anggraeni Dewi (Journal on Education, 2021)
The stage of human development in psychology is divided into several phases. In this case, the social psychology theory of development and behavior will be used to explore the patterns of social media influence. By using the case study method, this study aims to determine how the influence of Twitter social media on the national insight of adolescents. According to Erikson, adolescence begins at the age of 15-20 years. The main instrument that influences the national insight of the younger generation today is content from Twitter users themselves, as well as from influencers or public figures who provide knowledge or introduce new mindsets in dealing with national issues. Sometimes it is just to add the national insight that Twitter users have. The purpose of writing this article is to find out how teenage Twitter users are able to accept existing content and how it affects their national insight